ASSESSMENT OF PAIN AND FUNCTIONAL DISABILITY IN PATIENTS WITH KNEE OSTEOARTHRITIS: A CROSS-SECTIONAL STUDY. - Dey, Indranil; Patra, Satotsna; Golder, Samir; Patra, Pritiranjan (Student’s Journal of Health Research Africa, 2025)
Background Osteoarthritis (OA) is a degenerative joint disease that leads to pain, stiffness, and functional limitations, significantly affecting quality of life. Knee OA, the most prevalent form, impacts multiple joint structures and causes progressive disability. Understanding the relationship between pain, functional impairment, and quality of life is crucial for effective management. This study assesses the correlation among knee osteoarthritis, pain, functional impairment, and overall quality of life. Methods This cross-sectional study was conducted at Hi-tech Medical College and Hospital, Bhubaneswar (2020–2022) with 800 participants aged 50–65 years diagnosed with unilateral knee OA. Pain was assessed using the Visual Analogue Scale (VAS), functional disability with the WOMAC index, and quality of life using the SF-36 survey. Statistical analysis was performed using SPSS version 20, with Pearson correlation applied to assess associations between pain, functional disability, and quality of life (p < 0.05). Results Among 800 knee osteoarthritis patients (70% females, mean age 56.82 ± 4.75 years), the mean pain intensity (VAS) was 5.42 ± 1.09, and the total WOMAC score was 56.89 ± 8.47. Pain and functional disability showed a significant correlation (r = 0.285, p = 0.01), and higher disability was associated with lower quality of life (PCS: r = 0.595, MCS: r = 0.415, p < 0.05). Conclusion Greater pain and functional disability significantly reduce the quality of life in knee OA patients. Effective pain and disability management strategies are essential for improving patient well-being. Recommendation Integrated management approaches focusing on both pain relief and functional rehabilitation are recommended to enhance the quality of life in patients with knee osteoarthritis.